Education styles in a family versus life aims and values preferred by young people. - Dubis, Małgorzata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The socio-cultural, economic and political outlook changes visible in the contemporary The article includes the source of research concerning the declared system of values and aims in life by the respondents. The results of behaviour styles in a family research have been discussed-all meanings, the frequency of particular education styles. The author also tried to show the connection between the family functioning and values chosen by children.
Keywords: family; parenting styles; values; life aims; young people